Sensitivity Analysis of Fatigue Behaviour of Steel Structure under In-Plane Bending - Kala, Z. (Nonlinear Analysis: Modelling and Control, 2006)
The aim of the present paper is to analyse the influence of some input quantities on the fatigue resistance of a steel structure. The steel element subjected to many times repeated in-plane bending moment was analysed. The fatigue resistance was defined as the number of cycles causing the initial crack size propagation up to the critical size. The variability influence of input random quantities on the fatigue resistance variability was studied by means of the stochastic sensitivity analysis. All input imperfections were considered to be random quantities. The Latin Hypercube Sampling (LHS) numerical simulation method (Monte Carlo type method) was used. It has been found by the stochastic sensitivity analysis that the fatigue resistance variability is most sensitive to the initial crack variability. The paper presented draws attention to the necessity of identifying the statistical characteristics of the initial crack size as exactly as possible because their random variability can largely influence the failure probability of a structure. Large diversity in applying the statistical characteristics of initial crack size by numerous specialists is illustrated by the list of international publications at the end of the present paper.